2008
DOI: 10.1088/0031-9155/53/12/008
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of the variability of indocyanine green kinetics and using structurala prioriinformation in dynamic contrast enhanced diffuse optical tomography (DCE-DOT)

Abstract: We investigated 1) the variability of the indocyanine green kinetics (ICG) between different cases in the existence of random noise changing the size of the imaging region, the location and the size of the inclusion, 2) the use of structural a priori information to reduce the variability. We performed two dimensional simulation studies for this purpose. In the simulations, we used a two-compartmental model to describe the ICG transport and obtained pharmacokinetic parameters. The transfer constant and the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For 2D case, our results are compared with another analytical method while simulations obtained by using Finite Element Method are used to validate both 2D and 3D cases. These simulations are obtained by solving the diffusion equation numerically with the Comsol Multiphysics solver [12, 5658]. …”
Section: Numerical Application and Validationmentioning
confidence: 99%
“…For 2D case, our results are compared with another analytical method while simulations obtained by using Finite Element Method are used to validate both 2D and 3D cases. These simulations are obtained by solving the diffusion equation numerically with the Comsol Multiphysics solver [12, 5658]. …”
Section: Numerical Application and Validationmentioning
confidence: 99%
“…In addition to regular phantom studies, due to significant improvement in data acquisition speed, for the first time, we were able to conduct a series of dynamic contrast enhanced DOT and MR-DOT phantom studies using indocyanine green (ICG) [5]. Our analysis shows that ICG kinetics curves obtained by the frequency domain DOT system have the potential to characterize the tumor permeability.…”
Section: Task 3 System Evaluation Through Phantom Studiesmentioning
confidence: 99%
“…Liquid compartments are made of varying concentrations of Intralipid (%10, F. K. Clayton, NC) and Indian ink (Winsor & Newton, England) in water. Details of the system calibration and image reconstruction have been thoroughly discussed in [4].In addition to regular phantom studies, due to significant improvement in data acquisition speed, for the first time, we were able to conduct a series of dynamic contrast enhanced DOT and MR-DOT phantom studies using indocyanine green (ICG) [5]. Our analysis shows that ICG kinetics curves obtained by the frequency domain DOT system have the potential to characterize the tumor permeability.…”
mentioning
confidence: 99%
“…In addition to these studies, Unlu et al (2008a) demonstrated simultaneous acquisition of enhancement kinetics of a MR and an optical contrast agent using a hybrid MR-DOT animal imaging system. Moreover, Cuccia et al (2003) used the six-parameter pharmokinetic model and presented a study of the dynamics of the ICG in an adenocarcinoma rat tumor model by the use of diffuse optical spectroscopy co-registered with MRI.…”
Section: Introductionmentioning
confidence: 99%